Perceptions regarding tobacco usage among adolescents & young adults in a district of Western Uttar Pradesh (India): a qualitative study - Davey, Sanjeev; Raghav, Santosh Kumar; Davey, Anuradha; Singh, Jaivir (International Journal Of Community Medicine And Public Health, 2017)
Background:Tobacco usage in adolescents & young adults of state Uttar Pradesh of India is rising to an alarming level; although strategies to curtail them are also running; but the rising usage, can be better known by exploring the role of their perceptions regarding the usage of tobacco. Methods:This cross sectional study was done on total 400 (200 adolescents aged: 10-19 years & 200 young adults aged 20-30 years) by simple random technique using in-depth-interview schedule for 3 months in district Muzaffarnagar (Uttar Pradesh) in India. Results:The 41% Adolescents (AD) and 54.5% Young Adults (YA) were using tobacco (X2 =5.0, P <0.05); and this was mainly in smoked form (62.1% in AD & 54.1% in YA) and that too in the form of cigarettes in AD (56.8%) and bidi in YA (69.4%). Majority of them had also no knowledge regarding harmful effects of tobacco usage in AD & YA groups (50% & 41.2% respectively). Only 39% of AD group and 23% of YA group wanted to quit tobacco in future, that too only for saving money (43.7%) in AD group as compared to 40% of YA group who wanted to leave tobacco to remain healthy despite the information regarding harmful effects of tobacco from family/educational institutions level (X2 =8.1, P <0.05). Conclusions:Tobacco usage perceptions among adolescents and young adults in rural area are not healthy; as per results of this in-depth analysis, for which serious efforts from multiple levels are required to safeguard the health of our future generations.